2019
DOI: 10.1093/aesa/say058
|View full text |Cite
|
Sign up to set email alerts
|

Interplanting Different Varieties of a Sweet Potato Crop to Reduce Damage by Oligophagous Insect Pests

Abstract: One complementary or alternative control measure to chemical insecticide is interplanting of plants that affect insect behavior. While few successes are known based on interplanting of different varieties of the same crop, such intra-crop interplanting may be effective against insects that feed on a limited range of plants and have persistent preference to one cultivar. Here, we report three field trials that examined the efficacy of intra-crop interplanting of sweet potato varieties, Ipomoea batatas (L.) Lama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Diploid fruits of some genotypes were sufficiently small, tart, sweet, and firm to thwart entirely D. suzukii feeding and oviposition. Hence, interplanting resistant and smaller disease-free blueberries with a thicker firmer skin could disrupt reproduction in local D. suzukii populations through repeated ovipositional failure ( sensu Ichinose et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Diploid fruits of some genotypes were sufficiently small, tart, sweet, and firm to thwart entirely D. suzukii feeding and oviposition. Hence, interplanting resistant and smaller disease-free blueberries with a thicker firmer skin could disrupt reproduction in local D. suzukii populations through repeated ovipositional failure ( sensu Ichinose et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the observation re: mulching above, the control practice of intercropping may be incompatible with large scale commercial-type sweetpotato production. An interesting, more complex form of intercropping where highly susceptible varieties are used sacrificially to pull pests away from less susceptible varieties (also called 'intracropping') has been tried for sweetpotato (Ichinose et al 2019). Varieties of sweetpotato that differ in SPW preference (see host plant resistance control tactic section) were tested in an experimental design with the two varieties in separate, but adjacent plots and resulted in one variety preferentially attracting weevils away from the other less preferred variety (Ichinose et al 2019).…”
Section: Intercropping and Barrier Plantingmentioning
confidence: 99%
“…)-a storage root forming legume-to avoid or significantly reduce weevil damage (Karuniawan, 2004). Ichinose et al (2019) indicated that intra-planting a sweetpotato cultivar preferred by weevils with a less preferred cultivar in the same field may reduce total weevil damage.…”
Section: Pest and Disease Managementmentioning
confidence: 99%